The Role of Green Marketing Strategies and Artificial Intelligence in Influencing Green Purchase Intentions in Malaysia - Areej, Ahmed; Asmaul Husna, Haris Fadzilah (UNIMAS IR, 2025)
Environmental degradation and the overconsumption of resources have intensified the urgency to adopt sustainable consumption patterns. In Malaysia, despite rising awareness, the actual adoption of eco-friendly products remains limited due to inconsistent consumer intentions and lack of targeted marketing. This study investigates the influence of green marketing strategies, specifically green innovation, green creativity, and green media on consumers’ purchase intentions, while examining the moderating role of artificial intelligence (AI) in enhancing the persuasive power of these strategies. Grounded in the Theory of Planned Behavior (TPB) and the Elaboration Likelihood Model (ELM), this study adopts a quantitative approach using SmartPLS-SEM to analyse data from 312 individual consumers across seven major Malaysian states. The findings reveal that all three green marketing strategies significantly influence purchase intentions, with AI positively moderating these relationships. These results not only validate the theoretical integration of TPB and ELM but also offer practical guidance for technopreneurs and marketers in designing AI-driven green marketing strategies that resonate with environmentally conscious consumers. This research supports Malaysia’s national sustainability agenda by promoting behavioral change through strategic green communication. Keywords: Technopreneurship, Green Marketing Strategies, Sustainability, Purchase Intention, Artificial Intelligence (AI).